Mémoires et patrimonialisation d’un passé antéislamique : Mubârak al-Mîlî et l’ethnogenèse du peuple algérien - Aomar Hannouz (L’Année du Maghreb)
From the very beginnings of Algerian independence, Algerian nationalists emphasized the country’s Arab-Moslem identity. The islamization of North Africa was the very foundation upon which the Algerian nation was to be built. The region’s ancient past was almost entirely excluded from oral memory and written history. Thanks to James McDougall’s work, History and Culture of Nationalism in Algeria, the foundational work on national construction by Tawfiq al-Madanî (d. 1983) is well documented. Yet the writings of another historian close to the Association of Algerian Ulemas, Mubârak al-Milî (d. 1945) were no less important. His Histoire de l’Algérie dans les temps anciens et modernes, written at the end of the 1920s, deals with the Maghreb’s classic and pre-Islamic history, exposing a peculiar and original viewpoint. Contrary to nationalist historiography, imposed following independence, al-Milî’s work bears witness to the crystallisation of parallel and competing narratives for the ethnogenesis and cultural history, this very process being the consequence of social and political rivalry. His ideas and discourse on the ancient history of Algeria not only overturns the values and arguments advanced in the colonialist discourse, but assimilates the ethnic categories and scientific theories advanced by French scholarly societies of the 19th century. The European narrative of ethnogenesis provided a model for conceptualization of the Algerian people’s collective memory. Our contribution is an attempt to analyse this ethnic engineering, and so to examine the modes by which this ethnic group was reactivated to culturally express an ethnic group and “imagined community”, which was itself dominated socially and politically.